2021
DOI: 10.48550/arxiv.2103.04054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Short-term Rational Lanczos Method and Applications

Abstract: Rational Krylov subspaces have become a reference tool in dimension reduction procedures for several application problems. When data matrices are symmetric, a short-term recurrence can be used to generate an associated orthonormal basis. In the past this procedure was abandoned because it requires twice the number of linear system solves per iteration than with the classical long-term method. We propose an implementation that allows one to obtain key rational subspace matrices without explicitly storing the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This phenomenon has been studied for the polynomial Lanczos case in [22]. A brief study of the problem for the rational Lanczos case can be found in [23].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…This phenomenon has been studied for the polynomial Lanczos case in [22]. A brief study of the problem for the rational Lanczos case can be found in [23].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The latter feature is particularly important for large scale problems, for which dealing with the orthogonal approximation basis represents one of the major computational and memory costs. To the best of our knowledge, this variant of the Riccati solver is new, while it is currently explored in [40] for related control problems and the rational Krylov space.…”
Section: Feedback Matrix Oriented Implementationmentioning
confidence: 99%